COVID-19 and Pregnancy. When are complications expected? - Gonçalves, Daniela Reis (2022)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a RNA virus that cause coronavirus disease 2019 (COVID-19). The clinical spectrum SARS-COV-2 infection ranges from asymptomatic infection to critical and fatal illness. The expression of host receptor for SARS-CoV-2 cell entry in placental tissue and the identification of SARS-COV-2 in the placental tissue supports that SARS-COV-2 infection may affect pregnancy outcomes. At the moment, there is some evidence of the impact of the infection in pregnancy and fetal outcomes especially in symptomatic cases. Objectives: The aim of this study was to review the current state of the art of SARS-COV-2 infection during pregnancy and risk of adverse maternal, pregnancy and fetal outcomes, and to assess when these outcomes are most likely to occur. Main text: Asymptomatic COVID-19 disease in pregnancy is common. When present, symptoms and signs are similar to those in nonpregnant individuals. Infected pregnant women have a higher risk of rapid clinical deterioration and symptomatic pregnant patients appear to be at increased risk of severe disease and death. There is no evidence of an increased risk of congenital abnormalities or pregnancy loss in women with COVID-19 during pregnancy. Vertical transmission does not seem to be common. There is an association between COVID-19 in pregnancy and preterm labour, cesarean delivery, preeclampsia and stillbirth. Conclusions: Maternal complications are expected in pregnant women with older age, obesity, preexisting comorbidities or unvaccinated. Adverse pregnancy and fetal outcomes are expected in pregnant women with symptomatic disease and when maternal infection occurs after 20 weeks of gestation.